The effects of nine types of exercise rehabilitation therapies on improving limb balance, cognitive and emotional function, and quality of life in elderly patients with Parkinson’s disease: a network meta-analysis of 55 RCTs - Mao, Jing; Xia, Yi; Hu, Yimin; Yao, Xuewu (Frontiers in Neurology, 2025)
BackgroundParkinson's disease (PD) is a common neurodegenerative disorder that primarily affects individuals over the age of 60. Impaired limb balance, cognitive decline, and emotional disturbances are core symptoms of PD, significantly impacting patients' quality of life. While medication can alleviate motor symptoms, its effectiveness in improving non-motor symptoms (such as cognitive and emotional disturbances) is limited, and long-term use may lead to adverse effects. In recent years, exercise therapy has garnered increasing attention due to its safety, accessibility, and potential to offer both motor and non-motor benefits, making it an important direction in PD rehabilitation research. This study systematically evaluated nine exercise rehabilitation interventions to provide evidence-based non-pharmacological alternatives for PD management.MethodsA systematic search of six major databases was conducted, and 55 randomized controlled trials involving 4,417 patients with Parkinson's disease were included. The outcome measures were evaluations of balance, cognition, Emotional Functions, and quality of life-related indicators. Stata 17.0 was used to perform a net meta-analysis to assess the relative effectiveness of each intervention and to test the consistency of direct and indirect evidence.ResultsExoskeletal Training (ET) was the most effective intervention for improving balance (SMD = −2.52, 95% CI [−3.38, −1.67], p < 0.0001), resistance training (RT) provided the greatest benefit for reducing Emotional Functions (SMD = 1.02, 95% CI [0.67, 1.38], p < 0.0001). In terms of enhancing cognitive function, mind-body exercise (MBE) emerged as the optimal choice (SMD = −1.42, 95% CI [−2.01, −0.84], p < 0.0001), while resistance training (RT) was most effective in improving quality of life (SMD = 1.83, 95% CI [0.41, 4.07], p < 0.0001).ConclusionDance (DA) is the most effective intervention for improving balance, while aquatic training (ABT) and resistance training (RT) are most effective for emotional regulation. Mind-body exercise (MBE) demonstrates exceptional efficacy in cognitive function, while resistance training has the greatest impact on improving quality of life. These findings provide evidence-based guidance for optimizing exercise-based rehabilitation for Parkinson's disease, supporting tailored interventions targeting specific symptom domains. Future research should focus on refining protocols to maximize treatment efficacy.